A Mobile App to Provide Evidence-Based Information About Crystal Methamphetamine (Ice) to the Community (Cracks in the Ice): Co-Design and Beta Testing - Birrell, Louise; Deen, Hannah; Champion, Katrina Elizabeth; Newton, Nicola C; Stapinski, Lexine A; Kay-Lambkin, Frances; Teesson, Maree; Chapman, Cath (JMIR Publications, 2018)
BackgroundDespite evidence of increasing harms and community concern related to the drug crystal methamphetamine ("ice"), there is a lack of easily accessible, evidence-based information for community members affected by its use, and to date, no evidence-based mobile apps have specifically focused on crystal methamphetamine. ObjectiveThis study aims to describe the co-design and beta testing of a mobile app to provide evidence-based, up-to-date information about crystal methamphetamine to the general community. MethodsA mobile app about crystal methamphetamine was developed in 2017. The development process involved multiple stakeholders (n=12), including technology and drug and alcohol experts, researchers, app developers, a consumer expert with lived experience, and community members. Beta testing was conducted with Australian general community members (n=34), largely recruited by the Web through Facebook advertising. Participants were invited to use a beta version of the app and provide feedback about the content, visual appeal, usability, engagement, features, and functions. In addition, participants were asked about their perceptions of the app's influence on awareness, understanding, and help-seeking behavior related to crystal methamphetamine, and about their knowledge about crystal methamphetamine before and after using the app. ResultsThe vast majority of participants reported the app was likely to increase awareness and understanding and encourage help-seeking. The app received positive ratings overall and was well received. Specifically, participants responded positively to the high-quality information provided, usability, and visual appeal. Areas suggested for improvement included reducing the amount of text, increasing engagement, removing a profile picture, and improving navigation through the addition of a "back" button. Suggested improvements were incorporated prior to the app's public release. App use was associated with an increase in perceived knowledge about crystal methamphetamine; however, this result was not statistically significant. ConclusionsThe Cracks in the Ice mobile app provides evidence-based information about the drug crystal methamphetamine for the general community. The app is regularly updated, available via the Web and offline, and was developed in collaboration with experts and end users. Initial results indicate that it is easy to use and acceptable to the target group.